Liquid crystal active nanophotonics and plasmonics: from science to devices - Abdulhalim II, Ibrahim (Journal of nanophotonics, 2012)
Liquid crystals (LCs) are made of molecules and layers of small nm sizes, hence by their nature they fall in the categories of nanoscale science, engineering, and technology. Their interaction with solid nanostructures has been a subject of interest since the early days of LC research, as their surface alignment processes are strongly related to the formation of nanogrooves upon mechanical rubbing, nanocolumns by the oblique deposition technique, nanopores in etched surfaces, and the formation of self-assembled nanolayers on solid surfaces. The field has been boosted after the latest developments in nanotechnology both in theoretical simulations and in the possible fabrication of nanoscale structures, such as subwavelength gratings, nanoporous materials, and nanoparticles. A new field of research has emerged that combines LCs with nanostructures. Because LC materials are switchable, a new family of active plasmonic and nanophotonic devices is emerging. Interesting fundamental research phenomena are being reported, as well as the development of improved devices. The interaction of LCs with nanostructures is not only of fundamental interest but can also be applied for novel devices.